The effect of the Perkins-Blyth model on learning some compound skills in soccer for second intermediate students - Hassan, Ahmed; Ali , Ishraq (Journal of Physical Education, 2023)
The aim of the research is to identify the effect of the Perkins-Blythe model on learning some compound skills in football for second-year intermediate students. The researchers used the experimental approach with two equal groups (experimental and control) with a pre and post test and the research population consisted of (125) students from the Anwar Al-Aimm'a Intermediate School for Boys in the General Directorate of Wasit Education. And (40) students were randomly selected. The sample was divided into two groups, with (20) students for each group and After conducting the process of homogeneity and equivalence in the pre-tests, the main experiment was applied according to the Perkins-Blythe model, and after data collection. The researchers concluded that the application of the Perkins-Blythe model had a significant impact to raising the level of students through the idea of the model, which gave an opportunity for the student to be a real contributor to the process of achieving educational goals. The researchers recommended the necessity of introducing the model into the teaching process by teachers in order to raise the level of skillful performance of students.